2008
DOI: 10.1186/1471-2164-9-220
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis mRNA polyadenylation machinery: comprehensive analysis of protein-protein interactions and gene expression profiling

Abstract: Background: The polyadenylation of mRNA is one of the critical processing steps during expression of almost all eukaryotic genes. It is tightly integrated with transcription, particularly its termination, as well as other RNA processing events, i.e. capping and splicing. The poly(A) tail protects the mRNA from unregulated degradation, and it is required for nuclear export and translation initiation. In recent years, it has been demonstrated that the polyadenylation process is also involved in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 43 publications
9
139
0
1
Order By: Relevance
“…4, lane 1). As shown in lane 1, both the TAP-tagged and native AtCPSF30 were identified at similar strength, suggesting that AtCPSF30 may exist as a dimer in CPSF (Hunt et al, 2008). AtFIPS5 was not confirmed by immunoblotting because of the lack of a specific antibody.…”
Section: Components Of the Arabidopsis Cpsf Complex Revealed By Protementioning
confidence: 96%
See 4 more Smart Citations
“…4, lane 1). As shown in lane 1, both the TAP-tagged and native AtCPSF30 were identified at similar strength, suggesting that AtCPSF30 may exist as a dimer in CPSF (Hunt et al, 2008). AtFIPS5 was not confirmed by immunoblotting because of the lack of a specific antibody.…”
Section: Components Of the Arabidopsis Cpsf Complex Revealed By Protementioning
confidence: 96%
“…It has been observed that some Arabidopsis CPSF orthologs, such as AtCPSF160, AtCPSF100, AtCPSF73-I, AtCPSF73-II, and AtCPSF30, are all localized in the nucleus (Delaney et al, 2006;Xu et al, 2006), which indicates that they might coexist in the same complex. Y2H assay data show some pairwise interactions between CPSF factors as well (Hunt et al, 2008). However, whether or not these proteins form a protein complex in vivo is not clear.…”
Section: Components Of the Arabidopsis Cpsf Complex Revealed By Protementioning
confidence: 99%
See 3 more Smart Citations